Inspiratory muscle training in intensive care unit patients: A Systematic review - Nurul Imam; Taufan Citra Darmawan; Khalifatus Zuhriyah Alfianti; Welmince Paulina Nggorong; Ananda Patuh Padaallah (Nursing and Health Sciences Journal (NHSJ), 2025)
Critical patients with ICU room treatment have high morbidity and mortality. Prolonged use of mechanical ventilation can result in a reduction in the strength of the respiratory muscles. The purpose of this review article is to explain the effectiveness of the implementation of IMT in Intensive Care Unit patients. The research design used the PRISMA guideline with a literature search strategy on the Scopus database (n=10), ProQuest (n=1), Web of Science (n=913), PubMed (n=291), and Google Scholar (n=800), with the keyword "Inspiratory Muscle Training OR IMT AND Intensive Care Unit OR ICU AND Breathing AND Ventilation". The selected articles used the Randomized Control Trial and Quasi-Experimental, Case, and Observational Cohort Study research designs. The year the source of the literature was taken is 2020-2024. The effectiveness of Inspiratory Muscle Training also depends on several factors, including the patient's specific health condition, the type of disease or injury, and the implementation and supervision of the exercise program. One of the benefits of IMT is increased respiratory muscle strength, reduced duration of mechanical ventilation, reduced risk of respiratory complications, and improved quality of life. Inspiratory Muscle Training (IMT) has shown effectiveness in various clinical contexts, including the ICU.